Evaluation of central neuropathic pain and its relationship with quality of life in patients with stroke: a cross-sectional study - Ertem, Uğur; İrdesel, Jale (The European Research Journal, 2022)
Objectives: In addition to other complications in stroke patients, central post-stroke pain (CPSP) is sometimes overlooked. Considering the morbidities it causes in patients, it turns out to be a very important problem. The aim of this study is to investigate the frequency of CPSP, the factors causing CPSP, and the relationship between the CPSP and the quality of life and ambulation of individuals. Methods: A cross-sectional study was conducted on a group of patients with stroke. One hundred forty stroke patients were included in the study. Pain (The Leeds Assessment of Neuropathic Symptoms and Signs Pain Scale), health-related quality of life (Short Form 36 Questionnaire) and ambulation (Functional Ambulation Classification) were evaluated. In addition, a special evaluation form was created for this study. With this form, demographic characteristics of the patients, stroke type, cerebral location and hemisphere affected in stroke were recorded. These data were collected for the period between May 2016 and January 2018. Patients were divided into two groups. Group 1 included patients with CPSP and Group 2 patients without neuropathic symptoms. Results: CPSP was detected in 23 of 140 patients. In terms of demographic data, only gender differences were found between group 1 and group 2. CPSP was statistically significantly higher in female patients. There was no significant difference between the two groups in terms of the affected cerebral region and stroke type, but CPSP was significantly more common in patients with left hemispheric involvement. Emotional role restriction, body pain, social funtion, general health and mental health subcategories of the SF-36 were found to be significantly lower in group 1 compared to group 2. Also ambulation was worse in patients with CPSP. Conclusions: It was concluded that CPSP is a common problem and negatively affects the quality of life of the patients. Therefore, CPSP should be recognized in the early period after stroke and treatments should be arranged accordingly.